2017
DOI: 10.1093/sleep/zsx153
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Improves Peri-menopausal Insomnia: A Randomized Controlled Trial

Abstract: Acupuncture for peri-menopause insomnia: a randomized controlled trial, http://www.chictr.org.cn/showproj.aspx?proj=12118 ChiCTR-IPR-15007199, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 38 publications
2
71
0
3
Order By: Relevance
“…Fu et al [38] 76 peri-menopausal women with insomnia Acupuncture PSQI Acupuncture can contribute to a clinically relevant improvement in the short-term treatment of PMI, both subjectively and objectively.…”
Section: Sleep Disorders Vasomotor Symptoms Menopausal Hormone Thermentioning
confidence: 99%
See 1 more Smart Citation
“…Fu et al [38] 76 peri-menopausal women with insomnia Acupuncture PSQI Acupuncture can contribute to a clinically relevant improvement in the short-term treatment of PMI, both subjectively and objectively.…”
Section: Sleep Disorders Vasomotor Symptoms Menopausal Hormone Thermentioning
confidence: 99%
“…Other non-pharmacological options such as acupuncture [38], mindfulness, reflexology, exercise, and yoga have shown some positive results in small groups, but these have yet to be confirmed in larger studies. A short-term randomized trial has found a positive effect of acupuncture on perimenopausal insomnia [38].…”
Section: Insomniamentioning
confidence: 99%
“…Insomnia is characterized by having difficulty falling asleep, frequent nocturnal wakings with difficulty falling back asleep [4] and unexplained pain. A study conducted by the National Institutes of Health estimates the prevalence of insomnia in menopausal women at 40-50% [5][6][7][8]. Women who experience poor sleep quality during the MT are more likely to have critical problems [9] such as depression, anxiety, memory and cognitive deprivation, cardiovascular disease and reduced quality of life [3,4].…”
Section: Background Backgroundmentioning
confidence: 99%
“…Acupuncture, an important part of Traditional Chinese Medicine (TCM), has been used for thousands of years in China to treat various diseases including sleep disorders [5]. Many studies have confirmed the efficacy of acupuncture for primary insomnia and related depressive disorders [16][17][18].…”
Section: Background Backgroundmentioning
confidence: 99%
“…In China, patients have multiple choices for treatment of insomnia, including acupuncture [4][5][6][7], traditional medicine (Chinese, Mongolian, Tibetan traditional medicine) [8,9] and concerns about western medicine [10], but psychotherapy is not very accessible, and even CBT-I isn't available in most hospitals. In Inner Mongolia, there is conventional Mongolian mind-body interactive psychotherapy (MMIP), doctors mainly use MMIP and traditional Mongolian medicine, and achieve better outcomes in multiple psychosomatic diseases than just using medication.…”
Section: Introductionmentioning
confidence: 99%